Geomorphology characterization of Ica basin and its influence on the dynamic response of soils for urban seismic hazards in Ica, Peru - Bernal Esquia, Yesenia Isabel (2018)
We evaluated the influence of the geomorphology of Peru’s Ica Basin on the dynamic response of soils of the city of Ica. We applied five geophysical methods: spectral ratio (H/V), frequency-wavenumber (F-J), multichannel analysis of surface waves (MASW), multichannel analysis of microtremor (MAM), and Gravimetric Analysis. Our results indicate that the soils respond to two frequency ranges: FO (0.4–0.8 Hz) and F1 (1.0–3.0 Hz). The F-K, which considers circular arrays, shows two tendencies with a jump between 1.0 and 2.0 Hz. MASW and MAM contribute to frequencies greater than 2.0 Hz. The inversion curve indicates the presence of three layers of 4, 16, and 60 m with velocities of 180, 250, and 400 m/s. The Bouguer anomalies vary between −17.72 and −24.32 mGal and with the spectral analysis we identified two deposits, of 60 m and 150 m of thickness. Likewise, the relationship between the velocities of 400 and 900 m/s, with the frequency = 1.5 Hz, allows us to determine the thickness for the layers of 60 (slightly alluvial to moderately compact) and 150 m (soil-rock interface). These results suggest that the morphology of the Ica Basin plays an important role in the dynamic behavior of the soils to low frequency.